Salinity Effect on the Microwave Backscattering of The Calm Water Surface - Muhammad Y.Al-Allaf; Sabah H.Ali (College of Education for Pure Sciences, 2005)
The present paper illustrates the experimental results of the salinity affecting the backscattering signal from the calm water surface at an actual temperature of (19.7c°). The measurements were performed as a function of incident angle and antenna polarization by utilizing a specially designed and constructed laboratory measuring set-up operating at frequency of (lOGHz/CW-mode). The experimental results shows that the effect of water salinity on the backscattered signal from calm water surface (i.e., no roughness surface) was insignificant at microwave frequency of (lOGHz), and the vertical polarization has been found to be relatively better as compared to the horizontal polarization. Theoretical calculations of skin depth of the adopted saline water were also carried out depending on the complex dielectric constant of water.